2008
DOI: 10.1002/bip.20916
|View full text |Cite
|
Sign up to set email alerts
|

Design, structural, and immuno‐analytical properties of antigenic bioconjugates comprising a β‐amyloid‐plaque specific epitope

Abstract: Immunotherapeutic approaches are investigated for treatment of neurodegenerative diseases of the Alzheimer's dementia (AD) type. The identification of a beta-amyloid-plaque specific epitope, Abeta(4-10) (4FRHDSGY10), recognized by therapeutically active antibodies from transgenic AD mice could provide the basis for the development of AD vaccines. Here we report on the synthesis, structural and immuno-analytical characterization of bioconjugates comprising the beta-amyloid(4-10) epitope as new vaccine lead stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Additionally, our evidence suggests that the Aβ–Fbg interaction might proceed by a new mechanism independent of the known Fbg knob-hole interaction. These previous findings supported a basis for the present study, which was focused on the identification of the essential amino acids within the Aβ4–10 [17] and Aβ17–40 [14] and Aβ17–42 [14] epitope sequences, and on the evaluation of their relative contribution to the interaction with Aβ-specific mono- and polyclonal antibodies [18].…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, our evidence suggests that the Aβ–Fbg interaction might proceed by a new mechanism independent of the known Fbg knob-hole interaction. These previous findings supported a basis for the present study, which was focused on the identification of the essential amino acids within the Aβ4–10 [17] and Aβ17–40 [14] and Aβ17–42 [14] epitope sequences, and on the evaluation of their relative contribution to the interaction with Aβ-specific mono- and polyclonal antibodies [18].…”
Section: Discussionsupporting
confidence: 83%
“…Our data not only sustain conclusions obtained by others with citrullinated or noncitrullinated Ags (12,34,39,40) but also raised the question of which peptide characteristic had a major impact in the ELISA results. Indeed, only a few works have investigated the influence of the biotin position or the epitope-biotin distance, on single epitope recognition (11,34,40). With various peptides encompassing a single epitope in different conformations we showed that biotin-epitope distance was the major significant parameter that influenced epitope recognition.…”
Section: Discussionmentioning
confidence: 91%
“…A fter the development of ELISA in the 70s (1,2), the discovery of the high avidin-biotin affinity (3,4) allowed researchers to precisely manipulate proteins/peptides in numerous ELISA constructs in the 90s (5). Today, although ELISA is used worldwide, for instance to detect and quantify Abs, some studies highlighted the influence of experimental parameters on the outputs of such assay (6)(7)(8)(9)(10), reporting that a small change in the structure of an epitope-presenting peptide could impact its recognition by Abs (11)(12)(13)(14) and thus our perception of the analyzed biological processes. This is particularly important for autoimmune diseases such as rheumatoid arthritis (RA) in which autoantibody profiling, specificity, and titers can be associated with pathophysiology mechanisms and impact diseases diagnosis or therapy management (15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Bard et al also reported that immunization with a full length Aβ peptide is not required to trigger an efficacious antibody response and that antibodies produced by immunization with small epitope peptides also significantly reduced neuritic pathology. Furthermore, Manea et al showed that bioconjugates generated by attachment of multiple copies of the Aβ(4‐10) epitope to carriers consisting of branched chain polypeptides displayed increased antigenicity and thus might be potential immunogens …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the mass spectrometric analysis of the mutant Aβ(4-10) peptides upon affinity binding to a monoclonal anti-Aβ(1-17) antibody showed complete loss of binding by Ala-site mutation of any residue of the Aβ(4-10) epitope. Surface plasmon resonance affinity determination of wild-type Aβ (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) to the monoclonal Aβ antibody provided a binding constant K D in the low nanomolar range. These results provide valuable information in the elucidation of the binding mechanism and the development of Aβ-specific antibodies with improved therapeutic efficacy.…”
mentioning
confidence: 99%